Penguatan Karakter Siswa MIM Bandar 1 Melalui Permainan Tradisional Engklek - Hastutik, Linda Sri; Sugiyono, Sugiyono; Burhanuddin, Afid (Scholarly Journal of Elementary School, 2021)
The aims of this research were: 1) to find out the application of the traditional engklek game in learning, 2) to find out what characters can be strengthened through the engklek traditional game. This research is a qualitative research using an ethnographic approach. The time of the study was February-July 2021. The research subjects were 5 MIM students (the 5 subjects were 3rd grade students) in Dusun Tratas Desa Bandar and two MIM teachers (a 3rd grade teacher and a principal). Methods of data collection used observation, interviews, and documentation. The data analysis used in this research were: (1). Data reduction, (2). Data presentation, (3). Conclusion drawing. The results of this study: 1) the traditional engklek game can be used as a medium, model, and learning approach in accordance with the 2013 curriculum. 2) character strengthening of MIM Bandar 1 students through traditional engklek games was in a fairly good category including honest characters, hard work, responsibility, and tolerance. In the aspect of understanding, almost all students were able to understand this engklek game.